2020
DOI: 10.1038/s41598-020-59802-w
|View full text |Cite
|
Sign up to set email alerts
|

Replacing the eleven native tryptophans by directed evolution produces an active P-glycoprotein with site-specific, non-conservative substitutions

Abstract: P-glycoprotein (Pgp) pumps an array of hydrophobic compounds out of cells, and has major roles in drug pharmacokinetics and cancer multidrug resistance. Yet, polyspecific drug binding and ATP hydrolysisdriven drug export in pgp are poorly understood. fluorescence spectroscopy using tryptophans (trp) inserted at strategic positions is an important tool to study ligand binding. In Pgp, this method will require removal of 11 endogenous Trps, including highly conserved Trps that may be important for function, prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…In summary, we constructed a CmABCB1 mutant that can quantitatively measure substrate binding to the inner chamber by replacing intrinsic Trp residues with Tyr and introducing an extrinsic Trp into the inner chamber. Because the intrinsic Trp residues from the mouse ABCB1 could be replaced without reducing function, 48 we predict that use of this strategy with mammalian ABCB1s would enable quantitative evaluation of the binding properties of its poly‐specific substrate binding pocket.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, we constructed a CmABCB1 mutant that can quantitatively measure substrate binding to the inner chamber by replacing intrinsic Trp residues with Tyr and introducing an extrinsic Trp into the inner chamber. Because the intrinsic Trp residues from the mouse ABCB1 could be replaced without reducing function, 48 we predict that use of this strategy with mammalian ABCB1s would enable quantitative evaluation of the binding properties of its poly‐specific substrate binding pocket.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, expression and purification a of Trp-less ABCB1 mutant was already reported. 48 These facts suggest that by replacing the Phe on TM6 and/or Met on TM12 with Trp, establishment of a more sensitive system that can allow for the measurement of the substrate binding constants for the mammalian ABCB1 is possible.…”
Section: Substratementioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, yeast ABC transporter Pdr5 mutants with altered drug specificity were identified [26], the Yarrowia lipolytica pheromone ABC transporter Ste6 was trained to export the initially poorly exported a-factor of Saccharomyces cerevisiae [27] and the RND drug efflux pump AcrB was screened for mutants that resisted inhibition by an efflux pump inhibitor [28]. In a recent study, the eleven tryptophane residues of murine ABCB1 were screened for functionally-neutral substitutions using site-saturation mutagenesis to generate a tryptophane-free functional ABCB1 variant for drug interaction studies [29].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse mdr1a Pgp (codon-optimized abcb1a, GenBank JF834158) was expressed in Pichia pastoris, and grown in fermentor cultures as previously described (Bai et al, 2011). Tobacco, Etch Virus protease (TEV)-cleavable Twin-Strep and His 6 -tags were engineered to the C-terminus to facilitate purification by tandem affinity chromatography on Ni-NTA and Strep-Tactin resins as described (Swartz et al, 2020), with the following modifications. Microsomal membrane preparations were solubilized at a concentration of 2-3 mg/ml keeping a constant ratio of detergent to protein of 4:1 (w/w).…”
Section: Protein Purification and Quantificationmentioning
confidence: 99%